Anxiety and depression as predictors of life satisfaction during pre-professional health internships in COVID-19 times: the mediating role of psychological well-being - Tito Betancur, Madona (2022)
Due to the emotional impact of COVID-19 on university students, the goal was to explore the relationship between anxiety, depression, psychological well-being, and life satisfaction among pre-professional interns. The research was carried out using an explanatory cross-sectional design, with the participation of 1011 pre-professional interns of 13 health networks from the department of Puno (Peru). Data were collected using the Satisfaction with Life Scale, Generalized Anxiety Disorder Scale-2, Patient Health Questionnaire 2, and the Psychological Wellbeing Scale. The main data analysis was carried out using the R statistical software, and implementing the confirmatory factor analysis technique, which evidenced that the explanatory model provides an acceptable value. Based on the above, a negative relationship between depression and life satisfaction, (β ¼ .60, p < .001) and a positive relationship between anxiety and life satisfaction (β ¼ .28, p < .001) was shown, in addition to a mediating effect of the psychological wellbeing related to depression and life satisfaction (p < .001). In conclusion, life satisfaction is explained concerning the degree of depression and anxiety, as well as the moderating effect of psychological well-being. Despite that, there is an urgent need to take preventive actions to strengthen the mental health of the pre-professional health interns, who have also been providing support during the COVID-19 pandemic.